Analysis of Factors Influencing the Public’s Decision to Choose Kopsyah Rabani Services in The City of Serang - Vera maria; Husniatun Nuronia; Muhammad Rehan Al Aziz; Muhammad Ikhwan Nur Rifk; Haifz Alif Alfathan; Ceasarni Yasmine; Ahmad Zaky; Imam Amyrul Anwar (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study investigates the factors influencing public decisions to choose the services of Koperasi Syariah Rabani in the City of Serang. The research focuses on five explanatory variables consisting of religiosity, trust, service quality, location, and promotion. A quantitative cross sectional survey design was employed involving respondents who had previously used or were currently utilizing the services of the cooperative. Data were collected through structured questionnaires distributed to between 100 and 150 eligible respondents selected using purposive sampling techniques. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The analytical procedures included validity testing, reliability testing, classical assumption testing, partial significance testing, simultaneous significance testing, and coefficient of determination analysis. The findings reveal that religiosity, trust, service quality, location, and promotion positively and significantly influence consumer decision making. Religiosity emerged as the most dominant determinant, followed by trust, service quality, location, and promotion. The model demonstrated strong explanatory capacity, indicating that both religious considerations and institutional attributes shape consumer preferences. The study provides theoretical contributions to Islamic consumer behavior research and practical recommendations for enhancing the competitiveness of sharia cooperative services.